Operating Cash Flow Analysis as a Financial Performance Measurement Tool - Istianah; Haliah; Andi Kusumawati (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study is to analyze and determine the current ratio obtained at PT Siloam International Hospitals Tbk in 2019 – 2021. The method used in this study is descriptive qualitative research method. From the results of the study, it can be concluded that the financial performance of PT Siloam International Hospital.Tbk in 2019-2021 is assessed from the operating cash flow ratio is stated to be not good, the performance is said to be not good so that the company must strive to increase cash from operating activities so that in the future the company's cash flow can run smoothly.